Discovery of potent and orally bioavailable inhibitors of Human Uric Acid Transporter 1 (hURAT1) and binding mode prediction using homology model. Issue 2 (15th January 2016) - Peng, Jianbiao; Hu, Qiyue; Gu, Chunyan; Liu, Bonian; Jin, Fangfang; Yuan, Jijun; Feng, Jun; Zhang, Lei; Lan, Jiong; Dong, Qing; Cao, Guoqing
Graphical abstract: This Letter describes the discovery of a series of potent inhibitors of Human Uric Acid Transporter 1 (hURAT1). Lead generation and optimization via 3D pharmacophore analysis resulted in compound41 . With an IC50 of 33.7 nM, 41 also demonstrated good oral bioavailability in rat (74.8%) and displayed a consistent PK profile across all species tested (rat, dog and monkey). Abstract: This Letter describes the discovery of a series of potent inhibitors of Human Uric Acid Transporter 1 (hURAT1). Lead generation and optimization via 3D pharmacophore analysis resulted in compound41 . With an IC50 of 33.7 nM, 41 also demonstrated good oral bioavailability in rat (74.8%) and displayed a consistent PK profile across all species tested (rat, dog and monkey).